The Impact of Leadership Style and Working Motivation for Employee Performance With Job Satisfaction as Intervening Variabel: Case Study at PT Jaya Abadi Denpasar - Witara, Ketut; Nugroho, Dodit Cahyo; Tatasari, Titis; Kurniasari, Laksmi Murni; Kurniawati, Yuli (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
This survey is a quantitative survey that was conducted with a sample of 55 employees from PT Jaya Abadi Denpasar utilizing the total sample/saturated sample/census approach. The goal of this study was to identify and assess the influence of leadership style and job motivation on job satisfaction and performance among employees of PT Jaya Abadi Denpasar. The results of the validity tests are valid, the results of the reliability tests are reliable, the results of the normality tests are the normal distribution of the study data, and the heteroscedasticity tests do not reveal any heteroscedasticity. A multicollinearity test reveals that there is no multicollinearity. The following are the study's findings, based on data analysis and discussion: 1. Leadership style has a major influence on employee work satisfaction at PT Jaya Abadi Denpasar. 2. Work motivation has a significant influence on employee work satisfaction at PT Jaya Abadi Denpasar. Job satisfaction has a substantial influence on staff performance at PT Jaya Abadi Denpasar. 4. The management style of PT Jaya Abadi Denpasar has a significant impact on staff performance. 5. Work motivation has a significant influence on the performance of employees at PT Jaya Abadi Denpasar. 6. In PT Jaya Abadi Denpasar, leadership style has a substantial impact on staff performance via work satisfaction. 7. Job satisfaction at PT Jaya Abadi Denpasar has a major influence on staff performance.